2021
DOI: 10.1055/s-0041-1736164
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT in Erdheim–Chester Disease in the Era of Multimodality Imaging

Abstract: Erdheim–Chester disease is a rare disease with systemic non-Langerhans cell histiocytosis, the diagnosis of which with conventional imaging modalities is challenging. We describe a case of a 73-year-old woman who was referred with a progressive history of bilateral proptosis. The magnetic resonance imaging (MRI) orbit demonstrated bilateral orbital masses with optic nerve encasement. A subsequent 18F-FDG PET/CT scan showed multi-organ disease with involvement of the orbits, pericardium, aorta, pararenal fascia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(77 reference statements)
0
1
0
1
Order By: Relevance
“…For instance, in a study by Arnaud et al, sensitivity and specificity analyses compared 18 F-FDG PET/CT scan to CT or MRI, revealing nearly 100% specificity but variable sensitivity across organ systems. Moreover, 18 F-FDG PET/CT scan helps choose the best site for biopsy [23] . Additionally, previous observations suggested that 18 F-FDG PET/CT scan avidity may precede radiographic evidence of sclerosis in ECD, warranting exploration of whether avidity precedes changes in other imaging modalities in future studies [24 , 25] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study by Arnaud et al, sensitivity and specificity analyses compared 18 F-FDG PET/CT scan to CT or MRI, revealing nearly 100% specificity but variable sensitivity across organ systems. Moreover, 18 F-FDG PET/CT scan helps choose the best site for biopsy [23] . Additionally, previous observations suggested that 18 F-FDG PET/CT scan avidity may precede radiographic evidence of sclerosis in ECD, warranting exploration of whether avidity precedes changes in other imaging modalities in future studies [24 , 25] .…”
Section: Discussionmentioning
confidence: 99%
“…La infiltración de la grasa perirrenal y la fibrosis retroperitoneal puede ser observada mediante una TAC y el compromiso pericárdico o de aurícula derecha, en RMN cardíaca 8 . Sin embargo, el PET CT con F18 FDG tiene un papel fundamental al diagnóstico, ya que ayuda a determinar la extensión de la enfermedad, identificar posibles sitios de biopsia 9 , y también es de utilidad para evaluar la respuesta al tratamiento 10 .…”
Section: Discussionunclassified